Deciphering nitrogen removal mechanism through marine anammox bacteria treating nitrogen-laden saline wastewater under various phosphate doses: Microbial community shift and phosphate crystal. (April 2021) - Si, Pinkun; Li, Jin; Xie, Wenxia; Dong, Huiyu; Qiang, Zhimin
Graphical abstract: Highlights: Nitrogen removal through MAB was first studied under various phosphate doses. MAB activity was enhanced with 5–30 mg/L PO4 3− -P in saline wastewater treatment. Nitrogen removal performance through MAB was worsened at 160–400 mg/L PO4 3− -P. Calcium magnesium phosphate sediments were formed at high PO4 3− -P doses. Abstract: The effect of phosphate on marine anammox bacteria (MAB)-dominated anammox process in nitrogen-laden saline wastewater was first investigated. The activity of MAB was enhanced by dosing low concentrations of phosphate (5–30 mg/L PO4 3− -P), and the time of complete ammonium removal was shortened by 0.5 h. When PO4 3− -P exceeded 160 mg/L, the calcium magnesium phosphate precipitation was formed in the reactor. The contact between substrates and biomass was hindered by the sediments, and the nitrogen removal performance of MAB was also worsened. At 400 mg/L PO4 3− -P, the ammonium removal rate and nitrite removal rate decreased to 0.45 and 0.43 kg/(m 3 ⋅d), respectively. During the 158-day operation, MAB was still the dominant strain, but its relative abundance decreased by 15.4% at 400 mg/L PO4 3− -P. Besides, the presence of sediments stimulated the production of extracellular polymeric substances and the maximum yield reached 11.25 mg/g⋅wet weight at 200 mg/L PO4 3− -P.